Inside the digital revolution : policing and changing communication with the public - Wessels, Bridgette (Ashgate Pub., 2007)
In this work, Bridgette Wessels offers a unique insight into the ways in which core public institutions and powerful organizations develop digital communications and services within the public realm. The book draws on her ethnographic research with the London Metropolitan Police Service which, working in a socially, culturally and demographically complex city, offers a highly revealing case study of technology and human processes.